ANALITICAL HIERARCHY PROCESS (AHP) DALAM MELAKUKAN SELEKSI LOKASI DI PERUM PERUMNAS - Bahril - Datuk (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
The Perum Perumnas (Perusahaan Umum Pembangunan PerumahanNasional) a government company in housing development. The official name ofcompany in English is National Urban Development Company (NUDC). Themission of company is develop Low Cost Housing for the lowest and middleincome group of the peoples, specially in urban area. Perumnas must to get thebest location to develop the housing (to meet some criterias). For Medan case, wehave 3 candidates location, ie. Simalingkar about 10 km south-west of Medan,150Ha and former rubber plantation; Mandala about 8 km east Medan, 200 Ha andformer Palm Plantation and Martubung about 12 km north of Medan, 300 Ha andformer Rice Plantation.